Assessment of EGM2008 over Britain using vertical deflections, and the problems with historical data - Featherstone, Will; Olliver, J (Maney Publishing, 2013)
Vertical deflections synthesised from the Earth Gravitational Model 2008 (EGM2008) agree with astrogeodetic vertical deflections observed over mainland Britain to within ~1.2" RMS (north-south) and ~1.4" RMS (east-west), which is commensurate with values reported for North America, Australia and parts of continental Europe. For this assessment in Britain, there has been the additional need to transform the observed relative vertical deflections to absolute ones. Not applying horizontal datum transformations led to spurious results, so absolute vertical deflections must always be used to assess EGMs. Three datum transformations were trialled (three-parameter, seven-parameter and OSTN02), which show similar results when considering the estimated ~0.3" precision of these historical (1950 to 1976) astrogeodetic observations. Several other problems were encountered because of the historical nature of the data, comprising destruction of survey pillars, ambiguous station names, and a mixture of horizontal geodetic datums available in Britain.